ILLUSTRATING EVENTS: A STUDY OF HISTORY, MEMORY AND TRAUMAINGRAPHIC NARRATIVE - DEB, PRITHWA (International Journal of Psychosocial Rehabilitation, 2020)
Dealing with history and trauma in a limited space of that comics offer creates urgency for a sustained discussion of the form of the comics as well as the content. The readers/viewers are engaged in seeing the sequence of events through the panels. Reading the images and the texts create a challenge to come to a complete understanding of the text. But the contemporary graphic novelists/artists have dealt effectively with the medium of verbal-visual space. The paper deals with three texts, Art Spigelman’s Maus, Joe Sacco’s Palestine and Malik Sajad’s Munnu: A Boy From Kashmir. These texts span across different geo-political contexts which also helps in probing a comparative study of this genre. The personal, the historical and cultural trauma and the role of memory have been discussed in the paper and how the meaning is produced through images and a few dialogues in a limited and compact panel.